From Screens to Streets: Role of Digital Literacy and Misinformation in Shaping Democratic Participation in Nepal - Timalsina , Dhurba Prasad (Journal of Innovation in Academia, 2025)
The rapid growth of digital platforms in Nepal has reshaped democratic participation but also intensified misinformation, undermining informed citizenship and electoral trust. This qualitative study uses in-depth interviews and phenomenological analysis to explore how Nepali citizens engage with digital political content. Four major themes emerged: Digital Literacy as Situated Competence, Interpretation of Political Content, Misinformation and Democratic Trust, and Informal Misinformation Detection Strategies. Findings show digital literacy is deeply contextual, influenced by socio-cultural norms, gender gaps, and informal learning rather than formal education. Participants often respond emotionally to political information and depend on trusted social networks for validation. Misinformation erodes trust, leading to political disengagement or polarization. Yet, communities develop adaptive strategies to identify falsehoods. The study highlights the need for culturally sensitive digital literacy initiatives, stronger platform accountability policies, and community-based civic education to bolster democratic resilience.